DAY CENTERS OF ATTENTION TO MINORS: SOCIAL EDUCATOR COMPETENCES LIKE A FIGURE OF REFERENCE - Juan Manuel Sánchez Ramos, Jesús García Mínguez, (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The social uprooting is a factor of risk to bearing in mind at the moment of working with persons near to the processes of marginalization and failure to adapt. The compensation of social supports constitutes an added value that there offer the Day centers of Attention to Minors, as strategy of the factors and indicators of risk. In most cases this attribute liberates unnoticed, but yes implemented in an undeliberate way. This position leads us to thinking that the Social Educator of these devices exercises functions in the one that in many cases is unconscious.The article that we sense beforehand springs from a research on the incident that the educational programs of the Day centers exercise in minors, teenagers and families. Likewise, this research reveals the paper that the educators of the program develop as figures of social support. The research is carried out in a Center by day of attention to minors, teenagers and families in risk of social exclusion. The study has developed departing from the qualitative approach, making concrete in a research etno-methodologic, supported on the experiences and experiences of minors, teenagers, their progenitors and other agent social. The results of this study reveal how the social educator, from the affective links, does that the users of the program perceive not to be alone before the adversity, raising the motivation for transforming and to reconstruct their social situation, simultaneously that maximize the factors of social well-being and the indicators of risk diminish, The analysis of content shows that the educational processes of the Day centers turn the professionals into figures of reference by means of strategies of mediation, accompaniment, orientation and advice.